Nobiletin suppresses high‐glucose–induced inflammation and ECM accumulation in human mesangial cells through STAT3/NF‐κB pathway. Issue 3 (30th November 2018) - Liu, Zhenzhou; Han, Yanru; Zhao, Fucheng; Zhao, Zhenxia; Tian, Junlei; Jia, Kui
Abstract: Diabetic nephropathy (DN) is a complication of chronic diabetes and the main cause of end‐stage renal disease all over the world. Inflammation and extracellular matrix (ECM) accumulation play important roles in the pathogenesis of DN. Evidence suggested that nobiletin acts anti‐inflammatory role and plays a critical role in diabetes; however, its role in DN remains unclear. In the current study, we promulgated the nobiletin involved in high‐glucose–induced glomerular mesangial cell inflammation and ECM accumulation. Nobiletin treatment significantly abrogated high‐glucose–induced glomerular mesangial cell proliferation. Nobiletin treatment markedly suppressed inflammation cytokine secretion, including interleukin (IL)‐1β, IL‐6, tumor necrosis factor α, and monocyte chemoattractant protein 1 in high‐glucose–induced glomerular mesangial cell. Also, exposed nobiletin to high‐glucose–induced glomerular mesangial cell considerably reduced ECM accumulation through inhibited ECM‐associated protein type 4 collagen and fibronectin expression. Furthermore, nobiletin treatment abolished nuclear factor κB (NF‐κB) pathway activation through signal transducer and activator of transcription 3 (STAT3) inhibition. Overexpression STAT3 reversed the effects of nobiletin on high‐glucose–induced glomerular mesangial cell proliferation, inflammation, ECM accumulation, and NF‐κB pathway activation. Hence, our results suggest that nobiletin play roles in high‐glucose‐induced glomerular mesangial cells through inhibiting inflammation and ECM accumulation, and the STAT3/NF‐κB pathway was involved in the function of nobiletin. Abstract : Nobiletin exerts nephroprotective effects on high‐glucose–induced glomerular mesangial cells through inhibiting inflammation and ECM accumulation, and the signal transducer and activator of transcription 3 (STAT3)/nuclear factor κB (NF‐κB) pathway was involved in the function of nobiletin in diabetic nephropathy (DN).